HUBUNGAN ANTARA SISTEM INFORMASI MANAJEMEN KESISWAAN DAN KEPEMIMPINAN KEPALA SEKOLAH DENGAN PENGAMBILAN KEPUTUSAN OLEH KEPALA SEKOLAH DASAR KECAMATAN TEMPULING DAN KEMPAS KABUPATEN INDRAGIRI HILIR - Basyir Basyir; Isjoni Isjoni; Azhar Azhar (Jurnal JUMPED (Jurnal Manajemen Pendidikan), 2017)
In making effective decisions lot of things to consider, it can cover the basicissues that are used in decision making, types of decisions, the involvement of people(subordinates) to make decisions, form of decision-making, and the effectiveness of decisionmakingby the leadership. Recognizing the importance in decision making for organizations,especially schools, the principals need to increase capacity in decision making so that decisionstaken effectively and have a good impact. Decision-making related to the importance of theprincipal, the school is expected to have management information systems specifically studentinformation management system to support decision-making and have a good leadership stylein making decisions. This study aims to investigate the relationship between the variables (1)student information system management with decision-making, (2) the principal’s leadership indecision-making, (3) management information systems student and school leadership decisionmaking.This research is quantitative descriptive. The place of this research is the DistrictPrimary School Tempuling and Kempas Indragiri Hilir. The data in this study using a type ofprimary data and secondary data. The primary data of the raw data derived from respondentsto the questions that refer to variables of student management systems and leadership principalsuntil the end whether berberhubungan with decision-making in the District Primary SchoolTempuling and Kempas Indragiri Hilir. The primary data which will be processed. Whilesecondary data include a bibliography as well as material from the internet. While the source ofthe data in this study were principals included as samples. Analysis of the data used is descriptiveanalysis, inferential statistical analysis and hypothesis testing. Instrument reliability coefficientis calculated using Cronbach alpha. The results of this study show that: 1) there is a positiverelationship between management information systems student with decision-making at 0.580,2) there is a positive influence between the leadership of the principal decision-making amountedto 0.601, while simultaneously the influence of management information systems student andschool leadership with decision-making at 0.635.